Application of the Trans-Theoretical Model-Based Intervention on Smoking Behavior: A Systematic Review - Ichsan, Burhannudin (Universitas Muhammadiyah Surakarta, 2020)
Purpose: Smoking is a risk factor for various dangerous diseases. Smoking behavior is a public health problem that is difficult to be solved. Various interventions were carried out to stop smoking behavior. One of the interventions used to stop smoking behavior is an intervention based on the Trans theoretical model (TTM).Methodology: This systematic review used keywords: smoking AND (“trans-theoretical model” OR “trans theoretical model”) AND (male OR males) AND (adult OR adults) AND experimental. The data-bases used were: pubmed, science direct, google scholar, and opengrey. Narrative analysis was conducted to combine the articles. Results: The search resulted 996 articles. After reducing duplication, the number of articles were 964. Screening with titles and abstracts resulted in 11 articles. There were 5 articles that fit the eligibility criteria. There was one protocol article and 3 experimental articles related to the application of TTM to smoking cessation behavior.Applications/Originality/Value:: In general, the results showed that the TTM-based intervention for smoking cessation behavior worked well and gave good results as well.